The global shift away from fossil energy: A blind spot in climate foreign policy - Sonja Thielges (Stiftung Wissenschaft und Politik (SWP), 2023)
Climate experts are apprehensive about the approaching Presidency of the United Arab Emirates at this year's Conference of the Parties (COP) to the UN Framework Convention on Climate Change (UNFCCC). So far, the oil producer has not set a shining example with its climate protection efforts; and Sultan Al Jaber, this year's COP president, is head of the Abu Dhabi National Oil Company, one of the largest oil concerns in the world. To achieve the goal set by the Paris Climate Agreement of seeking to limit the average global temperature to 1.5 degrees Celsius above the pre-industrial level, the international community is striving for climate neutrality in the second half of this century. For this to happen, global energy systems will have to largely phase out fossil fuels, which, however, remain the dominant energy source. The fact that at present, a complete phase-out of fossil fuels cannot be expected is often lost in climate policy debates; in most countries, it is neither politically desired nor envisaged in long-term climate strategies. However, a speedy and orderly phase-down would have major benefits, such as providing the right investment incentives and supporting the necessary socioeconomic transformations in fossil-fuel producing countries. Today there is an urgent need to further develop the relevant policy and governance instruments as time is running out.
Keywords: 320; fossil energy; Conference of the Parties (COP); UN Framework Convention on Climate Change (UNFCCC); Paris Climate Agreement